Perspektif Ekonomi Kesejahteraan dalam Proyek Pembukaan Hutan di Papua - Iriyanti, Windy Army; Isnaini, Aninda; Bano, Rafly Parenta (Musamus Journal of Public Administration, 2024)
The aim of this research is to analyze the relationship between the concept of welfare economics and the social, economic and environmental impacts of land clearing projects in Papua for the 2009 – 2023 period. This research uses data on economic growth, percentage of poor people, and Gini ratio sourced from the Central Statistics Agency (BPS), as well as deforestation data from the global forest watch. The method used is descriptive analysis. The results of this research show that, although economic growth in Papua has increased along with large projects such as MIFEE, the food estate program, poverty and income inequality in Papua have not experienced significant improvements. Apart from that, environmental damage as described by externality figures in the form of deforestation also continues to increase.